2011
DOI: 10.1007/s00213-011-2440-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and molecular evidence for psychotropic effects in l-theanine

Abstract: Our results suggest that L: -theanine has antipsychotic-like and possibly antidepressant-like effects. It exerts these effects, at least in part, through induction of BDNF in the hippocampus and the agonistic action of L: -theanine on the NMDA receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 60 publications
4
47
2
Order By: Relevance
“…In contrast to the results reported here, a previous reported found that L-theanine (4, 20 or 100 mg/kg) had no effect on elevated plus maze behavior in C57BL/J mice when administered acutely or three times daily every other day for three weeks (Wakabayashi et al, 2012). Similarly, 10 mg/kg L-theanine (Heese et al, 2009) had no effect on elevated plus maze behavior in rats, but augmented the anxiolytic-like effects of midazolam (1.5 mg/kg), as well as decreased fine and basic motor movements in this assay (Heese et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the results reported here, a previous reported found that L-theanine (4, 20 or 100 mg/kg) had no effect on elevated plus maze behavior in C57BL/J mice when administered acutely or three times daily every other day for three weeks (Wakabayashi et al, 2012). Similarly, 10 mg/kg L-theanine (Heese et al, 2009) had no effect on elevated plus maze behavior in rats, but augmented the anxiolytic-like effects of midazolam (1.5 mg/kg), as well as decreased fine and basic motor movements in this assay (Heese et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, 10 mg/kg L-theanine (Heese et al, 2009) had no effect on elevated plus maze behavior in rats, but augmented the anxiolytic-like effects of midazolam (1.5 mg/kg), as well as decreased fine and basic motor movements in this assay (Heese et al, 2009). Other studies suggest that L-theanine produces antidepressant-like behavior in mice (Wakabayashi et al, 2012; Yin et al, 2011) and that when administered to newborn rats L-theanine improves performance in the object recognition memory test (Takeda et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that subchronic treatment with L-theanine elevated the swimming time and reduced the immobilization time in the FST. It has been already shown in Wakabayashi et al [45] that L-theanine restores the activity in FST.…”
Section: -Nitropropionic Acid (3-np)mentioning
confidence: 84%
“…14 This led the authors to suggest that the action of theanine may be mediated by the enhancement of calcium utilization via the NMDA receptor. Further support for this proposal has been recently provided by Wakabayashi et al, 15 who inter alia, found that L-theanine administration resulted in an increase in calcium release within cultured cortical neurons. The increase in calcium release was suppressed by both NMDA antagonists AP-5 and MIC-801.…”
Section: Effect On Brain Chemistry and Neurotransmissionmentioning
confidence: 74%